Answer:
45x happy to help ya :)
Step-by-step explanation:
Answer:bhwuwhn enshwh nehe
Step-by-step explanation:
Answer:
x = -7
Step-by-step explanation:
First we find the slope using
m = ( y2-y1)/(x2-x1)
= ( -8 - 5)/( -7 - -7)
= (-8-5)/(-7+7)
= -13/0
This means the slope is undefined and the line is vertical
Vertical lines are in the form
x= constant and the constant is the x value of the points
x = -7
<u>Answer:</u>
If f(x) = -3x - 5 and g(x) = 4x - 2 then (f - g)(x) = -7x - 3
<u>Solution:</u>
We need to determine the value of (f - g)(x)
Given that the function is f(x) = -3x - 5 and the other function is g(x) = 4x - 2
The value of (f - g)(x) can be found by as follows:
<em>(f - g)(x) = f(x) - g(x)</em>
On substituting the given value of f(x) and g(x) we get
(f - g)(x) = (-3x - 5) - (4x - 2)
Upon solving we get
(f - g)(x) = -3x -5 -4x + 2 = -7x -3
Hence the value of (f - g)(x) is equal to -7x - 3
What is the full question? This is just a statement.